Comparative analysis of high-temperature targets retrieved from SWIR and TIR data - Yu, Yifan; Pan, Jun; Du, Huishi (Frontiers in Environmental Science, 2024)
IntroductionForest fires, grassland fires, heap coking, straw burning, and volcanic eruptions are thermal anomalies. They attract attention and are designated as high-temperature targets. They can be retrieved macroscopically and quickly by remote sensing technology.MethodsIn temperature inversion, the mid-infrared (MIR, 3∼5 μm) and thermal infrared (TIR, 8∼14 μm) band data are most commonly used for temperature inversion. However, it is difficult to effectively retrieve the temperature of small-area high-temperature targets with them; the SWIR band data can perform this task more effectively. Additionally, inversion methods for short-wave infrared (SWIR, 1.3∼2.5 μm) and TIR band data are different. These differences lie in the mechanisms and models. Therefore, we use SWIR and TIR band data to retrieve heap coking temperature with Landsat 7 and Landsat 8 data.ResultsSWIR data obtained the results 496∼651 K and 912 K, and TIR data obtained the results 313∼334 K and 320 K.ConclusionThe SWIR inversion results have higher accuracy than the TIR inversion results. The inversion results are closer to the actual temperature of local coking. For this reason, SWIR is more suitable for temperature inversion of small-area high-temperature targets.